Modeling opportunity driven multiple access in UMTS. - Lin, P.
The Third Generation Partnership Project (3GPP) specification TR 25.924 proposed the opportunity driven multiple access (ODMA) mechanism for the universal mobile telecommunication system (UMTS). According to the maximum transmission bit rate that can be achieved between a UMTS Node-B and user equipment (UE), the coverage area of a Node-B is divided into two regions: high-bit-rate region (where a high bit rate can be used to deliver the packets for the UEs) and low-bit-rate region (where, due to hostile losses, the packets for the UEs can only be transmitted with low bit rate). The ODMA mechanism increases the transmission bit rate for the UEs in Region L by relaying the transmissions between a Node-B and UEs in Region L over a number of hops. However, more radio resource is consumed to serve a transmission with ODMA than that without ODMA, which may affect the quality of service (QoS) for other packet transmissions. In this paper, we propose an analytical model and simulation experiments to investigate the performance of the ODMA and non-ODMA networks in terms of the average transmission rate, packet blocking probability, and code channel utilization. Our study indicates that when the network traffic is not heavy, the ODMA mechanism significantly improves the average transmission rate and code channel utilization for the user packets by slightly reducing the QoS for other packet transmissions (i.e., packet blocking probability).
Keywords: QoS; UMTS; Universal Mobile Telecommunication Systems; Code channel utilization; Maximum transmission bit rate; Network traffic; Opportunity driven multiple access mechanism; Packet blocking probability; Packet transmission; Quality of service; Radio resource; User equipment